Resfriamento por ventilação: impactos na qualidade da carne de peru (Meleagris gallopavo) - Saggin, Rosemar Frigotto (2018)
Brazil was the third largest exporter of turkey cuts in 2016, whose main market was the European Union and which has a legal requirement regarding the percentage of water absorption and moisture / protein ratio. When using the combined cooling system (ventilation and sprinkling for 80 minutes and only ventilation for 8 hours and 30 minutes), the importer's standard of 0% moisture gain is met, but there is a high loss of water from the carcasses. The objective of this work was to optimize ventilation cooling parameters to minimize moisture loss and changes in the characteristics of turkey carcasses. Twenty male carcasses of the Nicholas lineage, with an average weight of 18.5 kg and age between 145 and 160 days, were selected. In the combined cooling (ventilation / sprinkling (VA) + ventilation (V) method), the carcasses had an average absorption percentage of -1.78%, with a weight loss of approximately 0.330kg / carcass. PH of 5.74, water retention capacity (CRA) of 56.2% and color with L * value of 71.76 were the results which showed that there are changes in the meat. To evaluate the cooling performed only by the sprinkler and ventilation system (VA), an experimental design with two replications was applied at the central point. The independent variables were water flow (m3 / h) and temperature (ºC). The best results were obtained in test 4, with a flow rate of 2.5 m3 / h of water and a temperature of -1 ° C. This variable was used, since the carcasses cooled under these conditions presented a percentage of absorption (+ 1,53%) that met the European regulation, with an approximate gain of 0,380 kg / carcass. The samples cooled by the ventilation and sprinkler system (VA), the result of CRA was 62.3%, the softness was 4.01kgf and the sarcomere length was 1.76μm. The ventilation and sprinkler system (VA) reduced the loss of water by evaporation, mainly from the less thick limbs and with greater area of contact with the environment. The Scanning Electron Microscopy (SEM) revealed inter-myofibrillar spaces between more curvilinear muscle bundles, suggesting that there was more hydration.